2013
DOI: 10.4103/0377-4929.125294
|View full text |Cite
|
Sign up to set email alerts
|

Is necropsy obsolete - An audit of the clinical autopsy over six decades: A study from Indian sub continent

Abstract: This study shows that therapeutic and preventive measures correctly instituted have significantly reduce the mortality, particularly with reference to cardiac and infectious causes. The discrepancy between antemortem and post-mortem diagnosis in 2010 is still very high at 9.30 percent. The autopsy will continue to remain relevant especially in elucidating the molecular cause of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…One covers a 63-year period from 1947 to 2010 and analyzes 591 randomly sampled autopsies. 27 Another report from the Post Graduate Institute of Medical Education & Research, Chandigarh, describes a comparative analysis of 1000 autopsies from 1982 to 1987. 28 In the present study, diagnoses were established using gross examination alone in 8951 of 13 024 patients (69%) and using both gross and histologic examination in 4073 of 13 024 (31%).…”
Section: Discussionmentioning
confidence: 99%
“…One covers a 63-year period from 1947 to 2010 and analyzes 591 randomly sampled autopsies. 27 Another report from the Post Graduate Institute of Medical Education & Research, Chandigarh, describes a comparative analysis of 1000 autopsies from 1982 to 1987. 28 In the present study, diagnoses were established using gross examination alone in 8951 of 13 024 patients (69%) and using both gross and histologic examination in 4073 of 13 024 (31%).…”
Section: Discussionmentioning
confidence: 99%
“…A study from India [ 10 ] described the discrepancies between antemortem and postmortem diagnoses in 591 patients over the years 1947 to 2010 and concluded that the number of discrepancies had decreased significantly over time, but that the discrepancy rate in 2010 was still high at 9.3 %.…”
Section: The Value Of the Autopsy In The Early 21st Centurymentioning
confidence: 99%
“…A similar study 20 showed in 2010 a discrepancy between ante-mortem and post-mortem diagnoses of 23.1%. However only 591 autopsies out of more than 6,300 disclosed enough data to be included in the paper, showing that even in medical centres with high autopsy rates, this procedure is considered with lack of reliability.…”
Section: Discussionmentioning
confidence: 72%
“…Since other causes are also evoked to the same effect, it may be very difficult to single out the role of the imaging techniques. Independently, the diminishing number of autopsies in many countries is a well established observation 11 , 19 , 20 . A large scale investigation with medical, sociological and epidemiological repercussions may be needed to determine the role of each factor in this issue.…”
Section: Discussionmentioning
confidence: 99%